Perspectives on transport pathways of microplastics across the Middle East and North Africa (MENA) region - Sisi Pu; Hooralain Bushnaq; Catherine Munro; Yann Gibert; Radhey Sharma; Vandana Mishra; Ludovic F. Dumée (npj Clean Water)
Abstract This perspective will focus for the first time on the occurrence and potential transport pathways of MPs within the MENA region. The delivery mechanism of MPs and characteristics of ocean currents and air patterns are discussed in detail within the Arabian Gulf -Gulf of Oman complex, the Red Sea-Gulf of Aden complex, the southern Arabian margin, and non-MENA region to the south, as well as the Mediterranean Sea respectively. Significant variable dissemination and seasonal delivery across different locations in the MENA regions are revealed from this analysis. The review provides guidance for researchers and government authorities in conducting MPs research and proposing actionable measures to mitigate risks associated with chemical and biological contamination.